Determinants of Halal Meat Certification Behavior in Indonesia: A TPB Analysis - Fuadi, Fuadi; Ramadhan, Muhammad; Batubara, Chuzaimah (Share: Jurnal Ekonomi dan Keuangan Islam, 2024)
Despite being the country with the largest Muslim population globally, Indonesia faces challenges in implementing halal food supply regulations, particularly in the meat industry. This study aims to explore the factors influencing the decision of actors in the halal meat supply chain in Aceh, Indonesia, to obtain halal certification for their products. Data was collected through structured interviews with 150 participants involved in the halal meat supply chain. The data analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The study applied the Theory of Planned Behavior (TPB) alongside government regulations on halal food and compliance to predict certification behavior through the intention to certify. The findings suggest that attitude, subjective norms, perceived behavioral control, halal regulation, and compliance influence the intention to certify, which in turn affects the behavior of the actors. This study demonstrates that intention to certify acts as a mediating factor in the relationship between these variables and the behavior of actors within the halal meat industry. These findings have substantial implications for both the halal food industry and regulatory bodies seeking to enhance halal certification rates in Indonesia.========================================================================================================ABSTRAK - Determinan Perilaku Sertifikasi Daging Halal di Indonesia: Analisis Theory of Planned Behavior. Meskipun merupakan negara dengan populasi Muslim terbesar di dunia, Indonesia menghadapi tantangan dalam implementasi regulasi penyediaan makanan halal, khususnya di industri daging. Studi ini bertujuan untuk mengeksplorasi faktor-faktor yang mempengaruhi keputusan pelaku dalam rantai pasokan daging halal di Aceh, Indonesia, untuk mendapatkan sertifikasi halal untuk produk mereka. Data dikumpulkan melalui wawancara terstruktur dengan 150 partisipan yang terlibat dalam rantai pasokan daging halal. Data analisis dilakukan menggunakan Structural Equation Modeling dengan Partial Least Squares (SEM-PLS). Penelitian ini menggunakan Theory of Planned Behavior (TPB) bersama dengan peraturan pemerintah tentang makanan halal dan kepatuhan digunakan sebagai kerangka teoritis untuk memprediksi intensi pensertifikasian produk. Hasil kajian menunjukkan bahwa sikap, norma subjektif, persepsi kontrol perilaku, regulasi halal, dan kepatuhan mempengaruhi intensi untuk mensertifikasi, yang pada gilirannya mempengaruhi perilaku pelaku. Studi ini menyimpulkan bahwa intensi memediasi hubungan antara variabel-variabel tersebut dengan perilaku pelaku usaha di industri daging halal. Kajian ini mempunyai implikasi yang sangat signifikan bagi industri makanan halal dan badan regulasi dalam meningkatkan tingkat sertifikasi halal di Indonesia.